1997
DOI: 10.1046/j.1365-294x.1997.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of the Greater Bilby Macrotis lagotis, a marsupial in decline

Abstract: The Greater Bilby has shown a rapid decline in range during this century and now occupies only a small isolated area in south-western Queensland (QLD) and a larger, but mostly low-density area in the north-western deserts of the Northern Territory (NT) and Western Australia (WA). We have examined variation in the control region of mitochondrial DNA (mtDNA) and at nine microsatellite loci in order to investigate the extent of current and historical subdivision across the species range, and to provide a prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…Mitochondrial haplotype diversity (H = 1.00) was very high, but nucleotide diversity was low (π = 0.028). These values are again comparable to intraspecific values for other Australian mammals (e.g., Pope et al, 1996;Moritz et al, 1997). The lack of fixed allozyme differences and sharing of mtDNA nucleotide substitutions among sampled populations is consistent with similar histories up until the end of the Pleistocene.…”
Section: Discussionsupporting
confidence: 81%
“…Mitochondrial haplotype diversity (H = 1.00) was very high, but nucleotide diversity was low (π = 0.028). These values are again comparable to intraspecific values for other Australian mammals (e.g., Pope et al, 1996;Moritz et al, 1997). The lack of fixed allozyme differences and sharing of mtDNA nucleotide substitutions among sampled populations is consistent with similar histories up until the end of the Pleistocene.…”
Section: Discussionsupporting
confidence: 81%
“…Home ranges of males overlapped considerably, indicating an absence of defended territories, but the extent of overlap may have been influenced by the size of the exclosure. Bilbies were found to maintain strict dominance hierarchies in captivity (Johnson and Johnson 1983), and Moritz et al (1997) found strong polygyny in a Queensland population study. Dominance in wild male bilbies may be maintained through temporal rather than spatial avoidance.…”
Section: Discussionmentioning
confidence: 96%
“…Macrotis lagotis [Moritz et al 1997]; Petrogale lateralis [Eldridge et al 1999]). Consistent with the expectation that island populations show reduced genetic diversity compared to mainland populations due to isolation and the susceptibility of relatively small populations to the effects of genetic drift (Frankham 1997), the genetic diversity on North Stradbroke Island was significantly lower than in the mainland Southeast Queensland koalas.…”
Section: Discussionmentioning
confidence: 99%